The role of heterotopic gastric mucosa with or without colonization of Helicobacter pylori upon the diverse symptomatology of Meckel's diverticulum in children - Oğuzkurt, Pelin; Talim, Beril; Tanyel, F. Cahit; Çağlar, Melda; Şenocak, M. Emin; Büyükpamukçu, Nebil (The Turkish Journal of Pediatrics, 2001)
The roles of heterotopic gastric mucosa either with or without colonization of Helicobacter pylori (HP) upon the diverse symptomatology of Meckel's diverticulum (MD) in children have been evaluated retrospectively. The medical records of 92 patients who underwent MD excision either incidentally or symptomatically between 1976 and 1997 were reviewed retrospectively. Age at admission and symptoms were recorded. The slides were stained with hematoxylin eosin and Giemsa to identify the presence of heterotopic tissue, ulceration, hemorrhage, inflammation and HP. Bleeding, obstruction and inflammatory groups were statistically compared with chi-square test. The age of the patients ranged between 1 day and 14 years with a mean of 3.5 ± 3.8 years. The male: female ratio was 3.6:1. Among 92 MD, 18 (19.5%) were removed incidentally, one of which had heterotopic gastric mucosa. The indications for surgical removal of MD were intestinal obstruction, diverticulitis and bleeding in 45 (48.9%), 11 (11.9%) and 18 (19.5%) patients, respectively. Heterotopic gastric mucosa was detected in 28 (30.4%) patients, of whom 8, 3, and 16 presented with intestinal obstruction, diverticulitis and bleeding, respectively.Helicobacter pylori was not detected in one patient with incidental removal of MD; with heterotopic gastric mucosa however, three patients with obstruction, one patient with diverticulitis and one patient with bleeding had HP in the heterotopic gastric mucosa located in MD. MD may become symptomatic due to a complicated course such as rectal bleeding, intestinal obstruction or diverticulitis. The presence of heterotopic gastric mucosa in MD seems to mainly associate with rectal bleeding. The presence of HP colonization in heterotopic gastric mucosa does not increase the incidence of rectal bleeding. The other complications of MD, including intestinal obstruction and diverticulitis, are not directly related to the presence of heterotopic gastric mucosa in the MD. However, colonization of heterotopic gastric mucosa by HP seems to increase the incidence of these complications.
Keywords: Meckel's diverticulum; heterotopic gastric mucosa; Helicobacter pylori